Analisis Portofolio Produk Harian KSP Gunung Slamet Cabang Ajibarang Menggunakan Matriks BCG - Evridanisa, Nayla Cahya; Nurhaliza, Putri Amellia; Argianto, Rifqi Tegar; Shafrani, Yoiz Shofwa (FEB Universitas Maritim Semarang, 2025)
To achieve optimal funding, an effective marketing strategy is needed for the success of the company. The Boston Consulting Group (BCG) Matrix functions as an analytical tool designed to improve performance through mapping between units based on growth rates and relative market share. This research is a field study with a qualitative descriptive approach. The focus of this study is the daily products of KSP Gunung Slamet Ajibarang Branch. The data collection methods applied by the researcher consist of observation, structured interviews, and documentation. The findings of this study describe the product position and strategies that can be implemented by considering market growth and existing market share. Daily products are in the cash cow category with market growth of 6.66% and a relative market share of around 1.10. Strategies that can be implemented include increasing productivity and quality to ensure competitiveness and provide value to consumers.